On the use of capture-recapture methods for studying swans - Bart, Jonathan (Wildfowl, 2013)
Capture-recapture methods are useful in estimating population size, survivorship, and other parameters when some animals alive in a given time period are not detected by the investigatorA large literature exists describing different capture-recapture models, and several user-friendly computer programs have been prepared to assist with the analysis. Investigators who mark swans (or other species) and then recapture or resight them at intervals might find these methods useful. I briefly review requirements and use of the models and computer programs and indicate howto obtain additional information about them.